Reticulocyte Count and Platelet Count as Predictors of Morphological Remission/Hemopoitic Recovery in Acute Lymphoblastic Leukemia (ALL) after Induction Chemotherapy - Huma Riaz, Hamzullah Khan, Shahtaj Khan, Sadaf Chiragh, (Journal of Rawalpindi Medical College, 2022)
Objectives: To determine the predictive values of reticulocyte and platelet count for remission in cases of acute lymphoblastic leukemia after induction therapy. Materials and Methods:This cross-sectional observational study was conducted in the department of hematology, MTI Hayatabad Medical Complex, Peshawar. All cases of ALL referred to the department for remission after taking induction therapy, irrespective of age and gender were included. Relevant information wascollected on a predesigned proforma prepared in accordance with the objectives of the study. Results: A total of 84 cases referred for remission were included, 56(66.7%) were males and 28 (33.3%) were females. 50(59.5%) cases were in the age range of 5-18 years. The mean with a standard deviation of the age of patients was 15+ 4 years. 75(89.3%) of the cases were classified into ALL-1) by FAB classification. 50(59.5%) of the referred cases had achieved morphological remission by bone marrow aspiration. There was a statistically significant rise in Platelet count of the remission vs non-remission cases (p-0.001). Again there was a statistically significant difference in the retic count of the cases with remission (p-0.05). We observed a statically significant downhill moderate correlation ofretic count with remission (in termsof blast count of BM aspiration) (p-0.04, r:-0.32). Platelet count also had an inverse significant correlation with remission ( p-0.01, r:-0.37). The diagnostic roles of the peripheral platelet count and retic yielded an area under curves of (0.768 and 0.648 respectively) to predict remission.We observed that the retic count and platelet count havebeen shown to have strong predictive valuesfor remission in ALL with interaction values of (R= 0.28**, ΔR²=0.02, p=0.08). Similarly, an increase in platelet also has a strong predictive value for remission in ALL cases with interaction values of (R= 0.41**, ΔR²=0.16, p=0.001) Conclusion: In ALL cases of post-induction therapy, The peripheral blood reading for an increase in Retic and platelet count predictsremission with 95% confidence. These values if strictly observed can reduce the frequency of invasive procedures like bone marrow aspiration. Keywords: ALL, Remission, Reticulocyte count, Platelet count.